Terapi Bermain dengan Media Menonton Video Animasi Kartun pada Anak Usia Prasekolah yang Menjalani Hospitalisasi di RST Dr. Reksodiwiryo Padang Tahun 2021 - Rischa Hamdanesti; Syalvia Oresti; Rezvigel Amanda; Delvi Afri Dilna (STIKes Alifah Padang, 2022)
There will be a crisis in the condition of the child being treated at the hospital because the child is stressed out by changes in both his health status and the environment in his daily routines, and because the child has a number of restrictions on coping mechanisms to deal with issues and stressful situations.Conducting first observations of teens at RST is a solution that may be used in community service projects. Dr. Reksodiwiryo is observing and speaking with kids receiving medical care at the hospital as part of a pre-test. Hold conversations with the head of the children's area to design and offer a location for play therapy to be provided. By watching animated cartoon movies and planning the activities' implementation, you may provide play therapy. The preparatory phase, dissemination of an overview of the activities, and shared viewpoint will be the methods used for execution. This activity will take place between March and April 2021. Watching animated cartoon videos is the way of implementation. 85 % of participants were eager and grasped the information offered, according to the activity's outcomes. The study's findings suggest that participants were able to adjust to the surroundings of the children's inpatient room, for example, by overcoming their fear of nurses and physicians.